Retention Strategies in Working With Justice-Involved Women. (July 2019) - Wickliffe, Joi; Kelly, Patricia J.; Allison, Molly; Emerson, Amanda; Ramaswamy, Megha
Research-based findings with vulnerable populations are strengthened by strong retention rates at the time of postintervention data collection. Women in the criminal justice system face a variety of gender-specific challenges including histories of childhood and adult sexual and physical abuse, substance abuse, untreated mental health problems, and chronic housing insecurity that can hinder follow-up of a research sample. The authors highlight a variety of retention strategies that they successfully used in their work with women following incarceration in local county jails.